2015
DOI: 10.1097/igc.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Unique Human Papillomavirus–Type Distribution in South African Women With Invasive Cervical Cancer and the Effect of Human Immunodeficiency Virus Infection

Abstract: A high number of women in South Africa with cervical cancer are HIV positive. Without viral cross-protection, HPV vaccines should prevent around 65% of cervical cancers in this population. Human papillomavirus type 45 infection is significantly linked to HIV and important for future vaccine developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…The current study demonstrated the high HPV/HIV co-infection of 24.4%, with high hr-HPV prevalence across almost all age groups and more multiple hr-HPV infection in HIV-positive women than compared to HIV-negative women. These findings are consistent with previous studies reporting higher prevalence of HPV [9, 27, 30, 35] and higher frequency of infection with multiple HPV types among HIV infected women [30, 32, 36]. A number of risk factors for HPV infection among women have been demonstrated in previous studies, including having more than one partner, early sexual initiation, age and marital status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study demonstrated the high HPV/HIV co-infection of 24.4%, with high hr-HPV prevalence across almost all age groups and more multiple hr-HPV infection in HIV-positive women than compared to HIV-negative women. These findings are consistent with previous studies reporting higher prevalence of HPV [9, 27, 30, 35] and higher frequency of infection with multiple HPV types among HIV infected women [30, 32, 36]. A number of risk factors for HPV infection among women have been demonstrated in previous studies, including having more than one partner, early sexual initiation, age and marital status.…”
Section: Discussionsupporting
confidence: 92%
“…According to Winer and colleagues, the actual first peak of HPV infection might be before the age of 25 years, as women are usually infected after sexual initiation [29]. HPV16 and 18 types have been found to be the most prevalent high risk types in most studies [4, 2628, 3032], yet in the current study we were not able to establish that. However, we observed high frequency of hr-HPV31/33/35/52/58 group types among the study population.…”
Section: Discussioncontrasting
confidence: 66%
“…Our findings that the prevalence and persistence of single, multiple, lrHPV and hrHPV infections was higher among HIV-positive compared to HIV-negative women are similar to other reports from SSA (31, 32) The increased prevalence and persistence of HPV infection in immunosuppressed individuals suggests that cell-mediated immune response may play an important role in the resolution and control of HPV infection (33). Although some studies have suggested that the association between HIV infection and increased prevalence of HPV infection and disease is related to the immunosuppression seen in HIV infection, there is also some evidence that mechanisms other than immunosuppression, such as direct molecular interactions between HIV and HPV viral genes, may influence the natural history of HPV (3437).…”
Section: Discussionsupporting
confidence: 90%
“…A study in neighbouring Burkina Faso found HPV35 to be the second most prevalent among sex workers with high prevalence of HIV [ 37 ]. Another study conducted in South Africa reported HPV35 as the third most prevalent genotype identified among 154 HIV-seronegative women with ICC [ 45 ]. Pirek et al [ 46 ] found HPV35 the fifth commonest among Cameroonian women with ICC and HPV45 was the second most prevalent type.…”
Section: Discussionmentioning
confidence: 99%